PENGOLAHAN LIMBAH HOME INDUSTRI GARMENT DENGAN TEKNIK PATCHWORK - Wati, Mursidah (Sainstek, 2009)
Research of Industrial Waste Home Processing of Garment with the Technique Patchwork have the character of the experiment aim to overcome will affect the industrial activity and also technology becoming especial source various environmental contamination occurence. Because have to be confessed by the industrial activity also have created the remarkable benefit for human being prosperity, among other things improve the a spark of life and the wide-speading of mobility usher the space. Gorontalo in growth nowadays industrial home of garment start a lot of popping out specially in subdistrict of south town of there are 99 industrial home of garment with the comparison sum up the resident of Subdistrict of Town of South arch of pursuant to resident report from Chief of village s/d of March month moon 2007 is: Men=15.590 soul, Woman=16.536 soul with the grand total= 32.126 soul. inferential how many waste which is in yielding by industrial home of garment as producer seenly is comparison sum up the resident of exist in subdistrict of town of south of town Gorontalo as consumer Along science growth, technological and art. Textile waste which at first changeable of no use by merekayasa is substance become the new form. with the technique patchwork is so that expected by through/passing processing of textile waste become the new textile form become the alternative can be seen to differ but own the energy wear high is and also enthused by the wide society.